Teaching mathematics using blended learning model : A case study in UiTM Sarawak Campus / Ling Siew Eng ... [et al.] - Siew Eng, Ling; Lee Al Lim, Elinda; Goh Tee Hiong, Kelvin; Beng Yong, Lee (2007)
This paper aims to determine the satisfaction level of the Pre-diploma (Science) students in using the blended learning model - a combination of face-to-face and online learning in MAT081 for the academic session of July — November 1995. In addition, it also examines the role of students and instructors in this learning mode. The preferred mix of faceto-face and online learning components was identified as well MAT 081 is a Basic Mathematics course with duration of 14 weeks with 5 study hours per week, Two groups of MAT 081 were offered in the semester of July — November 1995 and the students attended 4 hours of face-to-face learning and 1 hour of online learning per week in this blended learning mode. This study employed a mixed method design in which quantitative data was first collected through survey and followed by the qualitative data which would help to refine and explain the general picture obtained through quantitative data. A census survey was employed in the quantitative survey, while the students were stratified into 3 categories namely Good, Average and Poon before two were selected from each category to participate in the interview.The seven components identified to determine the satisfaction level of the. students on using blended learning model were adapted from a previous research done by Hisham Campton and FitsGerald (2004). They were the Content, Learner Interface, Feedback and Assessemnt, Personalisationt Learning Community, Access and Overall Satisfaction.The results showed that the students were satisfied with all components except for the component of Access. Basically, the students were less satisfied with this component.